Superelastic NiTi SMA cables: Thermal-mechanical behavior, hysteretic modelling and seismic application. (15th March 2019) - Fang, Cheng; Zheng, Yue; Chen, Junbai; Yam, Michael C.H.; Wang, Wei
Highlights: Superelastic shape memory alloy (SMA) cables are comprehensively studied. Thermal-mechanical characterisations of the SMA material are carried out. A series of SMA cable specimens are tested under various cyclic loading protocols. A simple yet effective numerical modelling method is proposed for SMA cables. A prototype bridge employing SMA cables as restrainers is designed and analysed. Abstract: This paper reports a comprehensive study on the mechanical behavior, annealing (heat treatment) scheme, hysteretic modelling strategy, and potential seismic application of superelastic shape memory alloy (SMA) cables. The study commenced with the thermal-mechanical characterization of monofilament SMA wires, and in particular, the influence of annealing scheme on the mechanical and phase transformation characteristics of the material was revealed. A series of 7 × 7 SMA cable specimens were subsequently tested at room temperature under various cyclic loading protocols. It is observed, among other findings, that the SMA cables are able to reasonably "scale up" the satisfactory properties of the SMA wires, and the mechanical behavior of the SMA cables may be improved by annealing. Moderate annealing temperature and duration (i.e., 350–400 °C for 15 min) can generally increase the stiffness, energy dissipation, and form setting ability of the SMA cables considered in this study, whereas an overly high annealing temperature tends to compromise these characteristics. Following the experimental study, an effective numerical modelling approach is proposed which reliably captures the basic mechanical behavior of the SMA cables. A model bridge, where SMA cables are adopted as restrainers, is finally designed and analyzed to demonstrate the efficiency of the SMA components for seismic damage mitigation. The analysis result shows that the SMA-cable restrainers can effectively control the peak and residual displacements of the bridge girder, and make the bridge more resilient.